“We should seize the opportunity to reach 1.3 million young people!” : Interview with Friedrich Hubert Esser, President of BIBB - Esser, Friedrich Hubert [Interviewter]; Jäger, Christiane [Interviewer] (My University, 2024)
"Waning trust in democratic institutions, increasing disenchantment with politics and a strengthening of extremist and populist leanings are topics which VET needs to tackle more than ever before. In November 2023, the Düsseldorf Chamber of Crafts and Trades conferred the Georg Schulhoff Prize on BIBB President Friedrich Hubert Esser. This award recognises outstanding services and contributions to VET made by persons and institutions. In his acceptance speech, Professor Esser highlighted how education for democratic citizenship is an important aspect of holistic VET. The significance of this for our liberal society and for future generations is a topic which he continues to pursue." (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; 370; Berufsbildung; Politische Bildung; Demokratie; Berufsbildungspolitik; Bundesinstitut für Berufsbildung